How do geography teachers notice critical incidents during instruction? - Scholten, Nina; Höttecke, Dietmar; Sprenger, Sandra (International research in geographical and environmental education, 2020)
Teachers are confronted with multiple stimuli during instruction. To teach responsively, they must be able to identify and address classroom incidents that are critical for student learning. In the literature, the term "noticing" is used to refer to teachers' perception and interpretation of such incidents, as well as the associated decision-making. This qualitative study explores geography teachers' ability to notice pertinent stimuli. For this purpose, two staged video vignettes of subject-specific critical incidents were constructed. Expert geography teachers watched the vignettes, stopping them to comment whenever they noticed something critical. The findings indicate that a majority of teachers perceived the incidents in the manner intended by the authors. Analysis of the teachers' comments revealed four types of interpretation. While the participants did not always make a decision about how to respond to an incident, the analysis also identified two types of decision-making.